1973
DOI: 10.1159/000175452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Pectin and Algin on Blood Cholesterol Level in Growing Rats Fed a Cholesterol-Free Diet

Abstract: The effect of dietary pectin and algin on blood cholesterol level of growing rats fed a cholesterol-free diet was studied. Pectin was found to lower blood cholesterol significantly while the effect of algin was very small. It was shown that the level of endogenic cholesterol in rats was lowered by feeding them a pectin which had a high content of methoxy groups and was highly viscous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 5 publications
(9 reference statements)
2
23
0
1
Order By: Relevance
“…The exception was the work of Delbarre et al '1977) where neither lemon pectin (approximately 40% esterified) nor apple pectin (degree of methoxylation 70%) was effective at a dose of 6 g/d. Studies in rats have suggested that only pectins with a high-methoxyl content are effective plasma cholesterol-lowering agents (Ershoff & Wells, 1962;Mokady, 1973). However, we have demonstrated a significant cholesterol-lowering effect for LMP in animal studies (Judd et al 1977).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…The exception was the work of Delbarre et al '1977) where neither lemon pectin (approximately 40% esterified) nor apple pectin (degree of methoxylation 70%) was effective at a dose of 6 g/d. Studies in rats have suggested that only pectins with a high-methoxyl content are effective plasma cholesterol-lowering agents (Ershoff & Wells, 1962;Mokady, 1973). However, we have demonstrated a significant cholesterol-lowering effect for LMP in animal studies (Judd et al 1977).…”
mentioning
confidence: 52%
“…HMP would therefore be expected to be more effective as a bile acid binding agent. Animal experiments (Ershoff & Wells, 1962;Mokady, 1973) have suggested this but we know of only one previous study in man in which pectin with a low-methoxyl content has been used, that of Delbarre et al (1977) and here neither HMP nor LMP lowered cholesterol levels, possibly due to the low doses (6 g/d) consumed by patients already on low-fat diets.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A predominantly bifidobacterial flora is considered to inhibit the growth of harmful bacteria such as pathogenic strains and protect infants against gastrointestinal diseases 14 . Consequently, factors that stimulate the growth of bifidobacteria appear to be promising effective substances for the maintenance of intestinal homeostrains.…”
Section: Discussionmentioning
confidence: 99%
“…Sweetpotato fiber is by far the most effective binder of cholesterol at 30%, cassava fraction at 3%, citrus pectin at 8% and the majority of samples at <20% for 28 fiber samples from a variety of commonly consumed tropical fruits and vegetables including sweetpotato 11 . It has been suggested that pectin with high methoxyl content is important in reducing serum cholesterol 14 . The methoxyl content of sweetpotato pectin was high at 9.7% of a cold water extract, the highest being for onion at 11% and wheat bran having only 0.1% in a study with a series of fruits and vegetables 5 .…”
Section: Discussionmentioning
confidence: 99%